2022
DOI: 10.3390/molecules27092995
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Antimicrobial Peptides as Antimicrobial and Antibiofilm Agents in Tackling the Silent Pandemic of Antimicrobial Resistance

Abstract: Just over a million people died globally in 2019 due to antibiotic resistance caused by ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species). The World Health Organization (WHO) also lists antibiotic-resistant Campylobacter and Helicobacter as bacteria that pose the greatest threat to human health. As it is becoming increasingly difficult to discover new antibiotics, new alternatives are needed to solve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 189 publications
0
12
0
Order By: Relevance
“…There is a scarcity of data regarding antibacterial and anti-biofilm effects of BMAP27-Melittin and NPs. A recent study revealed that insect peptides exert antibiofilm effects against major nosocomial pathogens via non-specific mechanisms (37). extracellular vehicles (EVs) from honeybees have exhibited antibiofilm effects against S. mutans and Streptococcus sanguinis (38).…”
Section: Discussionmentioning
confidence: 99%
“…There is a scarcity of data regarding antibacterial and anti-biofilm effects of BMAP27-Melittin and NPs. A recent study revealed that insect peptides exert antibiofilm effects against major nosocomial pathogens via non-specific mechanisms (37). extracellular vehicles (EVs) from honeybees have exhibited antibiofilm effects against S. mutans and Streptococcus sanguinis (38).…”
Section: Discussionmentioning
confidence: 99%
“…Dozens of recent papers described different attempts to reduce biofilm formation or to destroy an already-formed biofilm in order to avoid the removal or replacement of an implanted material. Enzymes, antimicrobial peptides, bacteriophages, and natural compounds from vegetal origins have been used, mainly in vitro, with variable results [ 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ]. Interesting observations were reported by Caballero Gomez in the field of meat-chain production using natural compounds extracted from essential oils alone or in combination with EDTA [ 133 ].…”
Section: Recent Attempts To Reduce/destroy a Biofilm During Infectionmentioning
confidence: 99%
“…Antimicrobial peptides, such as puroindoline A (PinA), melittin (AMP found in honeybees), nonribosomal lipopeptides, and tridecaptins (a group of cationic linear nonribosomal peptides) have certain inhibitory effects on Campylobacter spp., but most require combined treatment with antibiotics, and their effects on multiple Campylobacter spp. require further investigation [19]. Phage therapy is a promising strategy to ameliorate C. jejuni infections in livestock.…”
Section: Spread and Prevention Of Campylobacter Resistancementioning
confidence: 99%
“…Efforts are also being made to develop new ways to eliminate or reduce the economic harm of Campylobacter infections; for example, as a suitable replacement of the antimicrobial agents, the mixture of eugenol and trans-cinnamaldehyde could promote the growth of broiler chickens [18]. Alternative control strategies, including phage and antimicrobial peptide technologies, are considered promising approaches to reducing antimicrobial resistance (AMR) [7 ▪▪ ,19].…”
Section: Introductionmentioning
confidence: 99%